The Righteous Teacher in the Pesherite Commentaries - Wacholder, Ben Zion (Hebrew Union College annual, 2002)
This paper reopens the century-old debate as to the identities of the Righteous Teacher and his nemesis, the Wicked Priest. Scholarship takes it as axiomatic that the Righteous Teacher was the founder of the Essene Movement that flourished in Khirbet Qumran and equally, that the enemy of this מורה צדק (or Righteous Teacher) known by various sobriquets such as the Scoffer, Liar and Wicked Priest was his contemporary. But, the scrollists can not agree on the identity of these allegedly historical personalities. Neither has anyone been able to document their existence in history. In my opinion, however, the scrollists have misread these texts. I have contended that CD 1:11 ff. does not in fact claim what others allege, rather that the 390 years presaged had yet not elapsed at the time of this writing. This study deals with the passages in Pesher Habakkuk that relate the coming of the Righteous Teacher. Contrary to the entrenched opinion, what Pesher Habakkuk and other pesherite writings assert is that the Righteous Teacher will arrive at the End of Days. In other words, both the Righteous Teacher and the Wicked Priest are mythical personalities and recent scholarship concerning their identity is equally mythical.